Avaliação de dez gramíneas forrrageiras na região noroeste do Estado de São Paulo - Soares Filho, Cecílio Viega [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
O experimento foi desenvolvido de novembro de 1995 a julho de 1997, no município de Piacatu, região de Araçatuba – SP. Os tratamentos corresponderam a dez gramíneas forrageiras e 12 épocas de corte. Utilizou-se o delineamento de blocos completos casualizados com parcelas subdivididas e quatro repetições, estudando-se nas parcelas os seguintes capins: capim-Tifton 68 (Cynodon nlemfuensis Vanderyst cv. Tifton 68), capim- Tifton 78 (Cynodon dactylon (L.) Pers. cv. Tifton 78), capim-Tifton 85 (Cynodon spp. cv. Tifton 85), capim-Florakirk (Cynodon dactylon (L.) Pers. cv. Florakirk), capim-Florico (Cynodon nlemfuensis Vanderyst var. nlemfuensis cv. Florico), capim-Florona (Cynodon nlemfuensis Vanderyst var. nlemfuensis cv. Florona), capim-Coastcross (Cynodon dactylon (L.) Pers. cv. Coastcross 1), capim-Tifton 9 (Paspalum notatum Flüegge cv. Tifton 9), capim-Marandu (Brachiaria brizantha (A.Rich) Stapf cv. Marandu) e capim-Tanzânia (Panicum maximum Jacq. cv. Tanzânia 1) e, nas subparcelas, as 12 épocas de corte. Foram avaliadas as seguintes características: produção de massa seca (PMS), produção de massa seca de lâminas foliares (PMSLF), porcentagem de lâminas foliares (%LF), taxa de crescimento, teor e rendimento de proteína bruta (PB), teor de fibra em detergente neutro (FDN), teor de fibra em detergente ácido (FDA) e a digestibilidade “in vitro” da matéria seca (DIVMS). A PMS acumulada não diferiu (P>0,05) entre as espécies forrageiras. A PMS diferiu (P<0,05) entre as espécies forrageiras na estação das águas e na estação seca. Produções mais elevadas de MS foram obtidas na estação das águas, quando o capim- Tifton 85 foi superior (P<0,05) ao capim-Florico, não diferindo dos demais. Os resultados de PMSLF apresentados na estação chuvosa e seca diferiram (P<0,05) entre as forrageiras, observando-se que os valores mais elevados foram aqueles obtidos...

The experiment was carried out in the Northwest region of the State of São Paulo to evaluate ten grasses recently introduced in the region. The grasses studied were: Cynodon nlemfuensis Vanderyst cv. Tifton 68, Cynodon dactylon (L.) Pers. cv. Tifton 78, Cynodon spp. cv. Tifton 85, Cynodon dactylon (L.) Pers. cv. Florakirk, Cynodon nlemfuensis Vanderyst var. nlemfuensis cv. Florico, Cynodon nlemfuensis Vanderyst var. nlemfuensis cv. Florona, Cynodon dactylon (L.) Pers. cv. Coastcross, Paspalum notatum Flüegge cv. Tifton 9, Brachiaria brizantha (A. Rich) Stapf. cv. Marandu, Panicum maximum Jacq. cv. Tanzânia 1. The following variables were determined in two dry and two wet seasons: dry-matter (DM) production, DM production of leaf-blades (DMLB), percentage of leaf-blades, growth rate, “in vitro” dry-matter digestibility (IVDMD), yield of crude protein (CP) and the contents of CP, acid detergent fiber (ADF), and neutral detergent fiber (NDF). The accumulated DM production did not differ (P>0.05) among the grasses evaluated. The DM production differed (P<0.05) among the grasses in the wet-season and in the dry-season. Higher DM production were obtained in the wet-season, being the production of the cv. Tifton 85 greater (P<0.05) than that of Floricograss, but it did not differ of the other grasses. The DMLB presented in the wet and dry-seasons differed (P<0.05) among the grasses, being the higher values obtained in the wet season. In this season the DMLB of the cvs. Tifton 9 and Tanzânia were higher (P<0.05) than the production of the other grasses. The species evaluated showed similar growth rates. Higher contents of CP (125 to 145 g.kg-1) were observed in the cultivars of the genus Cynodon in the wet season. In the dry-season, contents of CP lower than 110 g.kg-1 were observed only in the cvs. Tanzânia (101 g.kg-1) and Marandu (97g.kg-1). Higher values of NDF were observed...(Complete abstract click electronic access below)
Keywords: Plantas forrageiras; Produtividade agrícola; São Paulo (Estado); Cynodon dactylon; Grass